Bacterial pathogens’ screening in Brazilian chigger mites (Trombidiformes: Trombiculidae), with the first report of 'Candidatus Rickettsia colombianensi'-like in avian-associated chiggers - Bassini-Silva, Ricardo [UNESP]; de Castro Jacinavicius, Fernando; Muñoz-Leal, Sebastián; Maturano, Ralph; Takatsu, Julia Carvalho; Tolesano-Pascoli, Graziela Virginia; Alquezar, Renata D.; Lugarini, Camile; Ferreira, Ariane; Moreira-Lima, Luciano; Welbourn, Cal; Ochoa, Ronald; et al. (Springer Nature, 2023)
Chiggers are larval ectoparasites of the Trombiculidae that can transmit pathogens to their hosts. In this study, chiggers collected from birds in Brazil were morphologically identified as Blankaartia sinnamaryi, Eutrombicula batatas, Eutrombicula daemoni, Eutrombicula goeldii, Eutrombicula tinami, and Parasecia gilbertoi. For these specimens, a beginning attempt at molecular identification were also provided, as well as, were genetically screened to detect bacterial pathogens. The species B. sinnamaryi and E. tinami were positive for Rickettsia felis-like and ‘Candidatus Rickettsia colombianensi’-like, respectively. For the other agents (Anaplasmataceae, Borrelia spp. and Orientia tsutsugamushi), the tests were negative. This is the first report of ‘Ca. R. colombianensi’-like and the second record of R. felis-like in chigger collected on birds from Brazil.
Keywords: Birds; Brazil; Chiggers; Ectoparasites; Rickettsia felis; ‘Candidatus Rickettsia colombianensi’